1996
DOI: 10.1046/j.1365-2125.1996.40021.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet PGI2 receptor affinity is reduced in pre‐eclampsia

Abstract: Platelet PGI 2 receptor affinity is reduced in pre-eclampsia WALTER KLOCKENBUSCH2, THOMAS HOHLFELD1, MICHAEL WILHELM1, THIERRY SOMVILLE2 & KARSTEN SCHRÖ R1 1Institut für Pharmakologie and 2Frauenklinik, Heinrich-Heine-Universitä t Dü sseldorf, Dü sseldorf, GermanyProstacyclin (PGI 2 ) receptors were studied in platelet membrane preparations from women with normal pregnancy, pregnancy-induced hypertension (PIH) or pre-eclampsia. Patient groups showed no differences in gestational week at delivery. A markedly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…However, the binding affinity of these receptors for the PGI 2 -mimetic iloprost was considerably reduced in preeclampsia compared with the other two groups. 129 Retrospective cohort studies of women with renal disease in pregnancy indicated that the incidence of preeclampsia was significantly less common in women treated prophylactically with heparin or aspirin. 130 Initial trials of low-dose aspirin in high-risk subjects appeared promising in the prevention of preeclampsia.…”
Section: Plateletsmentioning
confidence: 99%
“…However, the binding affinity of these receptors for the PGI 2 -mimetic iloprost was considerably reduced in preeclampsia compared with the other two groups. 129 Retrospective cohort studies of women with renal disease in pregnancy indicated that the incidence of preeclampsia was significantly less common in women treated prophylactically with heparin or aspirin. 130 Initial trials of low-dose aspirin in high-risk subjects appeared promising in the prevention of preeclampsia.…”
Section: Plateletsmentioning
confidence: 99%
“…Insufficient production of prostacyclin (PGI2) during early gestation is linked to the pathophysiology of pregnancyinduced hypertension (PIH). Aspirin, due to its anti-inflammatory and anticoagulant properties, is suggested as a possible effective treatment option for Preeclampsia [76][77][78][79][80][81][82][83]. Aspirin's ability to cross the placenta and work at 50-150 mg makes it a useful therapy, but >75 mg/day is better [84].…”
Section: Preeclampsiamentioning
confidence: 99%
“…Prostacyclin (PGI 2 ) may play a role in altered platelet-vessel wall interaction since reduced endothelial generation of this vasodilator and inhibitor of platelet function is well established in the disease [4,5]. Furthermore, there is no basis for the assumption that compensatory alterations at the receptor level counterbalance PGI 2 Klockenbusch/Goecke/Krüssel/Tutschek/ Crombach/Schrör deficiency in pregnancy-induced hypertension (PIH) and preeclampsia [6]. It is, however, uncertain whether PGI 2 really acts as an important mediator of blood flow in pregnancy.…”
mentioning
confidence: 99%